چوارچێوەی یاسایی پیادەکردنی ریفراندۆمی نیشتمانی لە باشووری کوردستاندا توێژیەنەوەیەکی یاساییە - د. عوسمان على وەيسى- زانكۆی لوبنانی فەرهنسی - هەولێر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Referendum is the most fundamental form of the national and democratic decisions to resolve vital constitutional and legal questions. According to international treatment, Kurdistan – as a land and people- were forcibly divided; the people of Kurdistan have been persecuted and suffered from internationally prohibited crimes Iraqi regimes, in flagrant violation of international agreements and those signed between Kurdistan liberation movement and central government in Baghdad. The federal authority in Baghdad did not respect the terms of the Iraqi constitution that was approved in 2005; thus the people of Kurdistan were subjected to unspeakable crimes on the hands of terrorist organization of DAESH and the federal government did not fulfill its obligations towards kurdish people. In the modern world, referendum is a convenient and democratic mechanism to take decision. The relevant institutions, the people of Kurdistan and the Kurdistan political leadership bear the burden carry out the referendum. It is imperative that international organizations be aware of such preparation, on the other hand, implementing the principle of partnership is a crucial element in legitimizing the disputed areas outside the Kurdistan region. it is very important for the ethnic and religious minorities living in Kurdistan region to support the referendum, freely and without any constraint. It is vital that from February 2016 the media organizations of the political parties to treat referendum as a national charter. Regional and international situation is favorable to the Southern Kurdistan to carry out such referendum, and if it is not done in 2016, it would be a great and irreplaceable waste of a once-in-a lifetime opportunity. Law allows a period of time between a referendum and declaring independence, and diplomatically it would be better to work on the subject of independence before declaring it. Special and expert commissions will deal with questions that arise after declaring independence such as the State of Iraqi responsibilities, agreements fulfilled by the Iraqi government, question of foreign debts, etc. It is very important that the date of the referendum coincides with one of the memorable and historical days of our nation. Organizing a proper propaganda for the referendum is decisive in order to elevate the general spirit of the population with regard to referendum. Anti-referendum provocation should be ignored and its arguments should not be debated. The speech of referendum front must be logical to ensure people that a brighter future awaits them. Every single member of the community must be ensured that the purpose of a referendum is not for the sake of doing it only; a referendum is to preserve and promote the interests of our ancestral homeland; its fallout will be dealt with seriously and decisively.